Quantifying the developed and developing worlds' carbon reduction contributions to Northern Hemisphere cryosphere change. (13th February 2019) - Yang, Shili; Dong, Wenjie; Chou, Jieming; Dai, Tanlong; Hong, Tao; Xiao, Cunde; Wei, Ting; Tian, Di; Ji, Dong
Abstract : Anthropogenically induced climate warming will not stop as long as carbon dioxide (CO2 ) emissions continue to increase. As positive feedback from the cryosphere can amplify climate warming in higher latitudes, adaptation to and mitigation of climate change in the cryosphere have become particularly important. In this study, we quantified the contributions of climate policies of the developed and developing worlds to moderating decreases in Northern Hemisphere sea ice and snow, using the Earth System Model of Beijing Normal University (BNU‐ESM). The results indicate that the sea ice extent and snow cover would continue to shrink as CO2 concentrations continue to increase, and the combined efforts of the developed and developing worlds could successfully reduce losses of Arctic sea ice and snow. In the medium term (before 2060), contributions of the developing world to reducing the loss of Arctic sea ice extent are expected to be 65% in JFM and 60% in JAS, while the corresponding contributions to reducing snow cover loss are 46 and 70%. These contributions from the developed world are smaller: 44% in JFM and 22% in JAS for sea ice extent and 34% in JFM and 20% in JAS for snow cover. Over the long term (until 2100), the developing world is expected to contribute 71% in JFM and 77% in JAS to reducing the Arctic sea ice losses, and its contribution to reducing snow cover loss is 73 and 66%. Similarly, the corresponding contribution for the developed world is also smaller: 36% in JFM and 24% in JAS for sea ice extent and 32% in JFM and 30% in JAS for snow cover. However, the developed and developing world achieves a combined mitigation effect of more than 90% in the near and long term. Abstract : Changes in atmospheric CO2 concentrations between 2006 and 2100 for scenarios ABNB (all counties follow business as usual emission pathway), ACNB (only developed world follow emission reduction pathway), ABNC (only developing world follow emission reduction pathway), and ACNC (all counties follow emission reduction pathway).